A Structural Functionalism Theory Review of the Prohibition of Sara Urang Marriage in Asir-Asir Village Central Aceh - Fattah, Al; Arresti, Fatma Tria; Rizki, Fitria Noviatur (Fakultas Syariah INSURI Ponorogo, 2024)
The purpose of this paper is to examine further how the tradition of the prohibition of sara urang marriage in Asir-Asir Village, Lut Tawar District, Central Aceh Regency, and how the structural functionalism theory reviews the tradition of the prohibition of sara urang marriage in Asir-Asir Village, Lut Tawar District, Central Aceh Regency. The type of research in this paper is empirical legal research using a sociological approach and the data sources used are primary data sources and secondary data sources. This research shows: First, the prohibition of sara urang marriage in Asir-Asir Village, Lut Tawar Subdistrict, Central Aceh Regency is based on the tradition of the prohibition of sara urang marriage and its purpose is to avoid social impacts when domestic conflicts occur. So, if you violate the tradition of the prohibition of sara urang marriage, you will be subject to sanctions in the form of parak (seclusion) and also muguleh koro (pay a fine). Second, the prohibition of sara urang marriage as a means of creating order in society is supported by the role of an active and interconnected community structure. This is by the theory of structural functionalism which explains that the relationship between interconnected elements will help to create order in society.